2019
DOI: 10.1590/1516-4446-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resistance exercise training and stretching on chronic insomnia

Abstract: Objective:The aim of this study was to assess the effects of resistance exercise and stretching on sleep, mood, and quality of life in chronic insomnia patients.Methods:Three 4-month treatments included: resistance exercise (n=10), stretching (n=10), and control (n=8). Sleep was evaluated with polysomnography, actigraphy, and questionnaires. Mood and quality of life were assessed with the Profile of Mood States (POMS) and the Medical Outcomes Study Short-Form 36-Item Health Survey (SF-36), respectively.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 36 publications
5
55
0
6
Order By: Relevance
“…No study could be selected for ayurveda, chelation, energy healing therapy, folk medicine, reiki, vitamin, massage, music therapy, and qi gong. Of the 40 studies selected, 12 focused on melatonin as possible intervention for insomnia disorder [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], 9 on meditative movement therapies [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ] (particularly, n = 1 on yoga [ 72 ], 6 on mindfulness [ 73 , 74 , 75 , 78 , 79 , 80 ] and 2 on tai chi [76.77]), 7 on exercise [ 81 , 82 , 83 , 84 , 85 , 86 , 87 ], 5 on natural herbal pharmacotherapy [ 88 , 89 , 90 , 91 , 92 ], 2 on light exposure [ 93 , 94 ], 2 on transcranial magnetic stimulation (rTMS) [ 95 , 96 ], 1 on homeopathy [ 97 ], 1 on hypnotherapy [ 98 ], and 1 on dietary supplements [ 99 ]. Two studies which evaluated exercise [ 82 , 83 ], one study evaluating melatonin [ 61 ], and...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No study could be selected for ayurveda, chelation, energy healing therapy, folk medicine, reiki, vitamin, massage, music therapy, and qi gong. Of the 40 studies selected, 12 focused on melatonin as possible intervention for insomnia disorder [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], 9 on meditative movement therapies [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ] (particularly, n = 1 on yoga [ 72 ], 6 on mindfulness [ 73 , 74 , 75 , 78 , 79 , 80 ] and 2 on tai chi [76.77]), 7 on exercise [ 81 , 82 , 83 , 84 , 85 , 86 , 87 ], 5 on natural herbal pharmacotherapy [ 88 , 89 , 90 , 91 , 92 ], 2 on light exposure [ 93 , 94 ], 2 on transcranial magnetic stimulation (rTMS) [ 95 , 96 ], 1 on homeopathy [ 97 ], 1 on hypnotherapy [ 98 ], and 1 on dietary supplements [ 99 ]. Two studies which evaluated exercise [ 82 , 83 ], one study evaluating melatonin [ 61 ], and...…”
Section: Resultsmentioning
confidence: 99%
“…Included studies focused on different age categories, specifically: 5 studies focused on children and adolescents (<18 years) [ 60 , 61 , 62 , 67 , 68 ], 23 studies focused on working-age adults (18–65 years) [ 70 , 71 , 72 , 73 , 75 , 78 , 79 , 81 , 82 , 83 , 84 , 86 , 87 , 89 , 90 , 91 , 92 , 94 , 95 , 96 , 97 , 98 , 99 ], and 2 studies focused on elderly (>65 years) [ 65 , 80 ]. Ten studies used mixed age samples with adult and elderly participants [ 63 , 64 , 66 , 69 , 74 , 76 , 77 , 85 , 87 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is postulated to be due to the beneficial impact of exercise on tension and anxiety and associated cognitive hyperarousal. 24 Studies from patients with inflammatory neuropathies (GBS and CIDP) that explored the impact of exercise on fatigue have reported mixed results. Although some have shown a beneficial impact of fatigue following a structured exercise program, others did not show an improvement in fatigue.…”
Section: Predictors Of Fatigue In Patients With Cidpmentioning
confidence: 99%
“…The study of D'Aurea et al (2018) (33) evaluated the effects of 4-month of resistance training and stretching programmes in treatment of insomnia. The authors found that both interventions are sufficient to promote significant improvement in Insomnia Severity Index scores, PSQI global scores.…”
Section: Discussionmentioning
confidence: 99%